História: A afirmação do Partido Republicano no Alentejo - Baiôa, Manuel (2022)
This article focuses on the affirmation of the Portuguese Republican Party in Alentejo (Portugal) in the last years of the Constitutional Monarchy. It analyzes the topics related to the organizational structures, at the level of the municipal and district commissions, and political centers of this party. The other topics analyzed were the press, the elite and the electoral results of the Portuguese Republican Party in the Alentejo region.